2009
DOI: 10.33549/physiolres.931858
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition as prevention and treatment of osteoporosis

Abstract: Osteoporosis is a systemic disease of the skeleton, characterized by reduction of bone mass and concurrent deterioration of bone structure. Consequently, bones are more fragile, and there is increased risk of fractures. The potential for acquisition of maximum bone mass is influenced by a number of factors. Among those are heredity, sex, nutrition, endocrine factors, mechanical influences and some risk factors. The best documented nutrient for metabolism of bone is calcium. Major role in the pathogenesis of os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…It is important to remember nevertheless that although the deterioration of the body during the aging process renders the older adult particularly susceptible to poor bone health, osteoporosis should not be considered a disease exclusively pertaining to elderly individuals as it globally affects millions of men and women of all ages and ethnicities (38,39). Bone mass is influenced by factors such as sex, hormones, as well as genetic and environmental variables and last, but not least, nutrition.…”
Section: Fruitmentioning
confidence: 99%
“…It is important to remember nevertheless that although the deterioration of the body during the aging process renders the older adult particularly susceptible to poor bone health, osteoporosis should not be considered a disease exclusively pertaining to elderly individuals as it globally affects millions of men and women of all ages and ethnicities (38,39). Bone mass is influenced by factors such as sex, hormones, as well as genetic and environmental variables and last, but not least, nutrition.…”
Section: Fruitmentioning
confidence: 99%
“…Previous in vivo and in vitro studies showed that boron has a wide variety of biological activities such as anti-osteoporotic [14], antioxidant [15,16], a regulator of the immune system [17,18], mineral and vitamin metabolism [19]. and steroid hormone metabolism [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Improved understanding of the physiopathology of osteoporosis has led to the development of pharmacological treatments targeting BMD, bone turnover and fractures. Lifestyle, nutrition and physical exercise are other parameters pertinent to prevent osteoporosis [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%